Heterozygous, Polyploid, Giant Bacterium, Achromatium, Possesses an Identical Functional Inventory Worldwide across Drastically Different Ecosystems. (10th November 2020) - Ionescu, Danny; Zoccarato, Luca; Zaduryan, Artur; Schorn, Sina; Bizic, Mina; Pinnow, Solvig; Cypionka, Heribert; Grossart, Hans-Peter
Abstract: Achromatium is large, hyperpolyploid and the only known heterozygous bacterium. Single cells contain approximately 300 different chromosomes with allelic diversity far exceeding that typically harbored by single bacteria genera. Surveying all publicly available sediment sequence archives, we show that Achromatium is common worldwide, spanning temperature, salinity, pH, and depth ranges normally resulting in bacterial speciation. Although saline and freshwater Achromatium spp. appear phylogenetically separated, the genus Achromatium contains a globally identical, complete functional inventory regardless of habitat. Achromatium spp. cells from differing ecosystems (e.g., from freshwater to saline) are, unexpectedly, equally functionally equipped but differ in gene expression patterns by transcribing only relevant genes. We suggest that environmental adaptation occurs by increasing the copy number of relevant genes across the cell's hundreds of chromosomes, without losing irrelevant ones, thus maintaining the ability to survive in any ecosystem type. The functional versatility of Achromatium and its genomic features reveal alternative genetic and evolutionary mechanisms, expanding our understanding of the role and evolution of polyploidy in bacteria while challenging the bacterial species concept and drivers of bacterial speciation.